2023
DOI: 10.11591/ijece.v13i3.pp3149-3160
|View full text |Cite
|
Sign up to set email alerts
|

Black spots identification on rural roads based on extreme learning machine

Abstract: <span lang="EN-US">Accident black spots are usually defined as road locations with a high risk of fatal accidents. A thorough analysis of these areas is essential to determine the real causes of mortality due to these accidents and can thus help anticipate the necessary decisions to be made to mitigate their effects. In this context, this study aims to develop a model for the identification, classification and analysis of black spots on roads in Morocco. These areas are first identified using extreme lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Overall results confirmed the efficiency of the proposed framework following feature selection and XGBoost algorithm implementation in industrial applications. Furthermore, authors' findings aligned with previous research where XGBoost was effectively applied in socioeconomical aspects namely medicine [33], [34], economy [35], cybersecurity [36], language processing [37] and environmental applications [38]. Regarding medical applications, feature selection and XGBoost was considered the most effective solution for heart disease classification with 99.6% accuracy [39] improving the solution of [40] where the proposed decision trees provided 97.75% accuracy.…”
Section: Resultssupporting
confidence: 77%
“…Overall results confirmed the efficiency of the proposed framework following feature selection and XGBoost algorithm implementation in industrial applications. Furthermore, authors' findings aligned with previous research where XGBoost was effectively applied in socioeconomical aspects namely medicine [33], [34], economy [35], cybersecurity [36], language processing [37] and environmental applications [38]. Regarding medical applications, feature selection and XGBoost was considered the most effective solution for heart disease classification with 99.6% accuracy [39] improving the solution of [40] where the proposed decision trees provided 97.75% accuracy.…”
Section: Resultssupporting
confidence: 77%
“…The rules generated by the general rule selection method encompass risk factors such as bridge, right shoulder width ranging from 0.5 to 1 meter, roadway width ranging from 8 to 12 meters, and dry roadway surface. A similar result from [25] demonstrated that roadway width, right shoulder width, and the presence of bridges have a significant effect on the severity level of black spots. These results are also 2081 consistent with the strategy of Morocco's road directorate for black spot identification.…”
Section: Resultsmentioning
confidence: 60%
“…Mbarek et al [46] developed a model using the extreme learning machine algorithm, ordinal regression, and XGBoost, which accurately identified black spots on rural roads in Morocco with an accuracy of 98.6%. According to the study, the significant factors contributing to accidents included pavement width, road curve type, and position.…”
Section: Machine Learning In Black Spot Identificationmentioning
confidence: 99%